White Extremism: Psychological Perspectives - Zora Arfina Sukabdi (Journal Psikologi Forensik Indonesia, 2025)
Whiteness is a fluid concept as the definition of “white” continues to change throughout history. In terms of social and political construction, whiteness is similar to the construction of race. The term “white”, although it was initially inspired by ‘being white’, does not simply refer to a person's skin color; but rather an ideology based on their views, values, behavior, habits and attitudes. This ideology leads to an unequal distribution of power and privilege. Implementing literature review, this article investigates the origins of the abbreviated "whiteness" in humans, as well as the signs of white extremism and the belief systems that support white extremism. Through this discovery it is known that the white color in humans has been visible for around 80,000 years. Furthermore, the most obvious evidence of white extremism is when violence is used as the only way to achieve goals, among other indicators. In terms of belief systems, the story of Noah and Abraham's families may have been the origin of the beliefs that led to the development of white supremacist ideas. Through a psychological lens, these findings may be useful to academics and practitioners in their efforts to understand white extremism.